2020
DOI: 10.1021/acsomega.0c00566
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Zero-Valent Iron Nanoparticles on Fremyella diplosiphon Transesterified Lipids and Fatty Acid Methyl Esters

Abstract: Efforts to enhance the transformative potential of biofuels is an important step to achieving an environment-friendly and sustainable energy source. Fremyella diplosiphon is an ideal third-generation biofuel agent due to its ability to produce lipids and desirable essential fatty acids. In this study, the impact of Nanofer 25s nanoscale zero-valent iron nanoparticles (nZVIs) on total lipid content and fatty acid composition of F. diplosiphon strains SF33 and B481 was investigated. We observed significant incre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 35 publications
1
9
0
1
Order By: Relevance
“…A similar observation was reported that the concurrent decreases of ROS and SOD supported the growth improvement with the involvement of 1.5 mg/L of ZnO nanoparticles . Recently, it was demonstrated that nZVI had a superior reducing capacity and hence alleviated the oxidative stress when attaching to microalgal surfacea or entering the cell interior . In addition, MDA and LDH were analyzed to track the extent of microalgal lipid peroxidation and membrane damage conditions.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A similar observation was reported that the concurrent decreases of ROS and SOD supported the growth improvement with the involvement of 1.5 mg/L of ZnO nanoparticles . Recently, it was demonstrated that nZVI had a superior reducing capacity and hence alleviated the oxidative stress when attaching to microalgal surfacea or entering the cell interior . In addition, MDA and LDH were analyzed to track the extent of microalgal lipid peroxidation and membrane damage conditions.…”
Section: Resultsmentioning
confidence: 99%
“…The nanoscale zerovalent iron nanoparticles (nZVI), a commonly favorable source of iron, possess several merits potentially resulting from its size being less than 100 nm, such as enhanced bioavailability, easy interaction with microalgal cell surfaces, promotion of iron uptake, and superior ability of being internalized by endocytosis . Additionally, nZVI might react with the extracellular organic matter secreted by the microalgae for ferrous ion generation, which is even more conducive for microalgal absorption .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…16 In recent years, iron nanoparticles, specifically nZVIs, have been applied to boost biomass production in cyanobacteria, and their impact on lipids and fatty acid methyl esters have been reported. 5,17 While the impact of iron deficiency and strategies to cope with this challenge have been extensively studied in other cyanobacteria species, 2 there is still insufficient knowledge of the impact of excessive iron on ROS generation in F. diplosiphon.…”
Section: Discussionmentioning
confidence: 99%
“…Various stressors such as ultraviolet radiation, high light intensity, and salinity are reported to increase oxidative stress by several folds, leading to cyanobacterial toxicity. , It is well known that in cyanobacteria, iron homeostasis is tightly controlled by the ferric uptake regulator which modulates the transcription of iron-responsive genes . In recent years, iron nanoparticles, specifically nZVIs, have been applied to boost biomass production in cyanobacteria, and their impact on lipids and fatty acid methyl esters have been reported. , While the impact of iron deficiency and strategies to cope with this challenge have been extensively studied in other cyanobacteria species, there is still insufficient knowledge of the impact of excessive iron on ROS generation in F. diplosiphon.…”
Section: Discussionmentioning
confidence: 99%